Sweden: From Neutrality to International Solidarity - Czarny, Ryszard M. (Springer International Publishing, 2018)
This book presents the legal and political factors determining international relations, including the processes of integration in all their complexity. The overall structure of the book, together with the composition of its separate chapters, allows for some general assumptions, identifying the main tendencies and placing them in a contemporary social context as well as establishing their relations with the practices of today. The content is a compendium of basic information and data related to the international processes which occur within specific formal, legal and political frames. The book is divided into five parts featuring not only deep historical context but most of all presenting current information and analyses of the last few years. Presented against the background and within the context of the Kingdom of Sweden's political system and its international environment, the book brings into the foreground issues of particular importance for Sweden's continuing European integration process and describes its response to the developments in the international situation.